Tadalafil and Sildenafil illicit association: Stability- indicating HPLC method, photodegradation kinetic and toxicological studies - Mayara Aramburú Pinto; Karine Favero Nicorena; Michel Mansur Machado; Luís Flávio Souza de Oliveira; Clésio Soldateli Paim; Fabiana Ernestina Barcellos da Silva; Marcelo Donadel Malesuik (Universidade de São Paulo, 2022)
Abstract The illicit market of counterfeit medicines containing sildenafil and tadalafil has been causing serious public health problems. Thus, further studies on this illicit association are needed. A stability-indicating HPLC method was developed for simultaneous determination of tadalafil (TAD) and sildenafil (SIL) using a C18 column (250 x 4.6 mm, 5 µm). Detection was achieved at 284 nm, for TAD, and 292 nm, for SIL. The method was considered to be specific, linear, precise, accurate, robust, and sensitive. In the photodegradation kinetic studies, the drugs showed a first-order reaction rate when isolated, and zero-order when associated. Toxicological assays demonstrated that the photodegraded drugs decreased cell viability in compared to non- degraded drugs, suggesting cytotoxic activity. Additional, mutagenic activity was not observed under the tested conditions. Photodegraded drugs, in association, depicted DNA damage index, suggesting genotoxic effects. The obtained results will be able to support the forensic intelligence laboratories, as well as to alert the population about the risk inherent to consuming counterfeit products.